Investigation of pre-service teachers’ attitudes towards teaching and professional self-efficacy beliefs according to their gender, programs, and faculties - Burhan ÇAPRİ; Öner ÇELİKKALELİ (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
The purpose of this study was to investigate the pre-service teachers’ attitudes towards teaching profession and their professional self-efficacy beliefs according to their gender, programs, and faculties. The research group included 158 male (63,2 %) and 92 female (36,8 %) senior students who are to be graduated from Education Faculty and Technical Education Faculty. The students were given “Attitude Scale Related to Teaching Profession”, “Self-Efficacy Perception Scale of Pre-service Teachers”, and “Personal Information Form” developed by the researchers. The findings revealed that while gender has an important effect on attitudes towards teaching, program and faculty variables do not have any significant effect. Also, it was found that gender, program, and faculty variables have significant effects on pre-service teachers’ self-efficacy beliefs. The findings were discussed according to the literature.